Juridical Review of the Rights and Obligations of Citizens According to Law Number 6 of 2018 concerning Health Quarantine - Theodorus Pangalila; Isye Junita Melo; Rico Septian Noor (JED (Jurnal Etika Demokrasi), 2023)
What obligations do the national authority, regional authority, and affiliated organizations have to uphold in the event of an outbreak of an infectious disease, an emergency of public health, or a scenario requiring quarantine? This study aimed to explain and prescribe the legal protection that is the right of citizens during the health quarantine period and sanctions for Indonesian citizens who do not carry out their obligations during the health quarantine period. This study's methodology is known as normative legal research, where the main characteristic of normative legal science research, the primary source is legal material which contains normative rules. In this study, what is meant is regulations regarding Health Quarantine. The study results indicate that there must be legal protection for the rights of Indonesian citizens during health quarantine based on Law Number 6 of 2018 regarding Health Quarantine. Furthermore, According to Law Number 6 of 2018 regarding Health Quarantine, there are penalties for citizens who fail to fulfill their commitments during health quarantine.